Development of Student Pancasila Character Instruments : A Evidence of The EFA, CFA and RASCH Models - Sakti, Hadi Gunawan; Rizka, Muhammad Arief; Ayu, Ieke Wulan; Ariany, Farida (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to compile and validate Pancasila character instruments using three methods: Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and the RASCH model. This research is a survey involving 681 students from universities throughout Indonesia. The study consisted of three stages, namely (1) item preparation, (2) construct validation through EFA and CFA, and (3) item validation using the RASCH model. The preparation of Pancasila character instrument items was carried out through a literature review and 44 statement items covering six aspects of Pancasila character. After EFA was conducted, 44 items were eliminated into 33 items which were divided into five constructs or factors, namely factor 1 = Ethics, Nationalism, Independent and Critical, factor 2 = Self Efficacy, factor 3 = Empathy, factor 4 = Creativity, and Global Knowledge, and factor 5 = Discipline. This result is reinforced by the CFA, which shows that the factors formed are in accordance with the model and have items that can describe the character of Pancasila (loading factor â‰¥0.3). Further analysis using RASCH shows that the instrument developed has good validity and reliability and can be used to measure students’ Pancasila character.